Research-related Tourism - Chetan, Shah; Trupp, Alexander * (Elgar Publishing, 2022)
The Encyclopedia of Tourism Management and Marketing is, quite simply, the definitive reference work in the field. Carefully curated by leading tourism scholar Dimitrios Buhalis, this is the largest tourism management and marketing ontology that has ever been put together and offers a holistic examination of this interdisciplinary field This is a 4-volume set. Volume 1 contains entries A–D, Volume 2 contains entries E–I, Volume 3 contains entries J–R and Volume 4 contains entries S–Z. Page numbers start from 1 in each volume.